Relationship between subclinical hypothyroidism during pregnancy and hypertensive disorder complicating pregnancy and its poor prognosis - W.X. Chen; L.Y. Tang (Clinical and Experimental Obstetrics & Gynecology)
Objectives: Pregnancy-induced hypertension syndrome (PIH) is a common disease of pregnant women. This study explored the correlation between subclinical hypothyroidism (SCH) and PIH and the prognosis of patients with PIH. Materials and Methods: The study included 180 pregnant women were divided into three groups, including PIH+SCH group, PIH+non-SCH group, and normal group. Immunofluorescence method was used to detect thyroid stimulating hormone (TSH). Student’s t-test and chi-square test were used to analyze the difference between two groups. Pearson correlation analysis was used to assess the correlation between two variables. Results: Systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were all significantly upregulated in PIH+SCH group compared with those in normal group and PIH+ non-SCH groups (all p < 0.05) and SCH had a close relationship with SBP (r 2= 0.2163, p = 0.0002). The incidences of postpartum hemorrhage, premature delivery, abortion, FGR, and pregnancy anemia were all cleary increased in PIH+non-SCH, and PIH+SCH groups, compared with those in normal group, respectively (8.3, 10, 13.3, 1 8.3, 23.3; 13.3, 23.3, 26.7, 35, and 36.7 vs.1.7, 5, 3.3, 1.7, and 5.1 (all p < 0.05). The incidences of premature delivery, abortion, FGR, and pregnancy anemia were significantly higher in PIH+SCH group than PIH+non-SCH group (23.3, 26.7, 35, and 36.7 vs. 10, 13.3, 18.3, 23.3 (all p < 0.05). Moreover, serum TSH level was significantly increased in high gestational week group compared with low gestational week group (6.86 ± 0.78 vs. 5.79 ± 0.45, p < 0.05) and SBP, DBP, and MAP were all remarkably elevated in high gestational week group compared with low gestational week group (167.6 ± 12.4 vs. 150.9 ± 10.8; 108.5 ± 11.4 vs. 95.2 ± 11.2; 121.8 ± 13.6 vs. 110.0 ± 12.3 (all p < 0.05). In addition, compared with those in low TSH group, the incidences of postpartum hemorrhage, premature delivery, abortion, FGR, and pregnancy anemia were all obviously increased in high TSH group (all p < 0.05). Conclusion: SCH had a close association with PIH and poor prognosis during pregnancy.